The homesman [large type] - Swarthout, Glendon, 1918-1992 (Wheeler Publishing, 2014)
Four women in the isolated frontier territory go mad, and it is up to the unlikely combination of homesteader Mary Bee Cuddy and ne'er-do-well Briggs to escort them east to safety.